Fingerprint Pattern of Matching Family with GLCM Feature - Bahtiar Imran; Karya Gunawan; Muhammad Zohri; Lalu Darmawan Bakti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
In this research, fingerprint pattern matching is done to find out whether there is the similarity between parent and child fingerprint pattern. An important step in fingerprint matching is the fingerprint pattern search and matching. Fingerprint data is used by 11 families from various families. The method used in fingerprint feature extraction is GLCM. The GLCM angle used is 0o, and the features used are contrast, homogeneity, correlation, and energy. For fingerprint pattern matching use minutiae score. From the results obtained GLCM has been widely used in fingerprint texture analysis. This study proves that the proposed method for matching fingerprints on parents and children gets the most dominant pattern is the loop pattern.